Chromatin dynamics during spermiogenesis. - Rathke, C.; Baarends, W.M.; Awe, S.; Renkawitz-Pohl, R. (Biochimica et Biophysica Acta, 2014)
The function of sperm is to safely transport the haploid paternal genome to the egg containing the maternal genome. The subsequent fertilization leads to transmission of a new unique diploid genome to the next generation. Before the sperm can set out on its adventurous journey, remarkable arrangements need to be made during the post-meiotic stages of spermatogenesis. Haploid spermatids undergo extensive morphological changes, including a striking reorganization and compaction of their chromatin. Thereby, the nucleosomal, histone-based structure is nearly completely substituted by a protamine-based structure. This replacement is likely facilitated by incorporation of histone variants, post-translational histone modifications, chromatin-remodeling complexes, as well as transient DNA strand breaks. The consequences of mutations have revealed that a protamine-based chromatin is essential for fertility in mice but not in Drosophila. Nevertheless, loss of protamines in Drosophila increases the sensitivity to X-rays and thus supports the hypothesis that protamines are necessary to protect the paternal genome. Pharmaceutical approaches have provided the first mechanistic insights and have shown that hyperacetylation of histones just before their displacement is vital for progress in chromatin reorganization but is clearly not the sole inducer. In this review, we highlight the current knowledge on post-meiotic chromatin reorganization and reveal for the first time intriguing parallels in this process in Drosophila and mammals. We conclude with a model that illustrates the possible mechanisms that lead from a histone-based chromatin to a mainly protamine-based structure during spermatid differentiation. This article is part of a Special Issue entitled: Chromatin and epigenetic regulation of animal development.